Freedom of Expression in the Era of the Privatization of Reason - Bjerre, Henrik Jøker (Academic Quarter | Akademisk kvarter, 2016)
The importance of free speech is beyond dispute in liberal democracy, and is today hardly challenged by anyone, but fundamentalist, religious groups. But which purpose should free speech serve, and how should it be (re)defined and administered in order to fulfill this purpose? I claim that these questions are more important than they may seem, and that they are easily overlooked, if free speech is treated as an end in itself or as something that one should not question at all. In the liberal tradition, freedom of expression was clearly valued for its excellent utility for the progress of society, but not for being an end in itself. In this article, I want, first, to make this point clear (through a reading of John Stuart Mill and Immanuel Kant) and, second, to offer a couple of suggestions for relevant discussions on the restrictions, regulations and reinventions of free speech that might be required today in order to sustain and revive the liberal tradition itself.